219k views
1 vote
3k(k+10)=0 factor show steps please

User Oblitum
by
4.8k points

1 Answer

4 votes

Answer:

Simplifying

3k(k + 10) = 0

Reorder the terms:

3k(10 + k) = 0

(10 * 3k + k * 3k) = 0

(30k + 3k2) = 0

Solving

30k + 3k2 = 0

Solving for variable 'k'.

Factor out the Greatest Common Factor (GCF), '3k'.

3k(10 + k) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'k' equal to zero and attempt to solve:

Simplifying

k = 0

Solving

k = 0

Move all terms containing k to the left, all other terms to the right.

Simplifying

k = 0

Subproblem 2

Set the factor '(10 + k)' equal to zero and attempt to solve:

Simplifying

10 + k = 0

Solving

10 + k = 0

Move all terms containing k to the left, all other terms to the right.

Add '-10' to each side of the equation.

10 + -10 + k = 0 + -10

Combine like terms: 10 + -10 = 0

0 + k = 0 + -10

k = 0 + -10

Combine like terms: 0 + -10 = -10

k = -10

Simplifying

k = -10

User Paxz
by
4.6k points